2020
DOI: 10.1111/ijcp.13812
|View full text |Cite
|
Sign up to set email alerts
|

The effects ofElaeagnus angustifoliaL. on lipid and glycaemic profiles and cardiovascular function in menopausal women: A double‐blind, randomized, placebo‐controlled study

Abstract: Aims The reduced production of ovarian hormones is considered to be the cause of an increase in the incidence of heart disease in women after menopause. Phytoestrogens are found in various herbal sources and are considered as an alternative to hormone therapy because of structural similarity with oestrogen. Elaeagnus angustifolia L., known as Senjed in Persian, is used in Iranian traditional medicine with various medicinal properties, contains valuable compounds, including two types of phytoestrogens. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 52 publications
(122 reference statements)
2
16
0
Order By: Relevance
“…Accordingly, its consumption is highly recommended to maintain health in elderly, especially women. In the present study and the continuation of our previous studies (Emaminia et al, 2020;Shabani et al, 2020), the effect of E. angustifolia on some serum hormones was studied in postmenopausal women for the first time.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Accordingly, its consumption is highly recommended to maintain health in elderly, especially women. In the present study and the continuation of our previous studies (Emaminia et al, 2020;Shabani et al, 2020), the effect of E. angustifolia on some serum hormones was studied in postmenopausal women for the first time.…”
Section: Discussionmentioning
confidence: 76%
“…Increased TSH levels also lead to hypercholesterolemia and hypertriglyceridemia (Wanjia et al, 2012). Although the decrease in PRL was not significant after treatment with herbal medicine, we previously showed that E. angustifolia treatment also significantly reduced LDL-C and improved cardiovascular function and lipid profile in postmenopausal women (Shabani et al, 2020). Therefore, it can be concluded that the overall effect of changes in the two hormones TSH and PRL after treatment with herbal medicine on the lipid profile and cardiovascular function was positive.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations